2021
DOI: 10.3389/fpsyg.2021.642593
|View full text |Cite
|
Sign up to set email alerts
|

Changes and Adaptations: How University Students Self-Regulate Their Online Learning During the COVID-19 Pandemic

Abstract: During the COVID-19 (coronavirus disease 2019) pandemic, universities had to shift from face-to-face to emergency remote education. Students were forced to study online, with limited access to facilities and less contact with peers and teachers, while at the same time being exposed to more autonomy. This study examined how students adapted to emergency remote learning, specifically focusing on students’ resource-management strategies using an individual differences approach. One thousand eight hundred universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
128
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(188 citation statements)
references
References 37 publications
7
128
1
6
Order By: Relevance
“…In line with these findings, early qualitative work suggests the pandemic has fostered opportunities for appreciation and gratitude by considering one's personal experience in comparison to others who have been adversely affected (i.e., relative fortune) and has increased time spent with family and engaging in new hobbies or activities [29]. However, burgeoning research has reported the negative impacts of the pandemic and national lockdowns on students' ability to regulate their attention and motivation levels [30] and to develop studying networks [31]. This was particularly true within our sample, with students reporting reduced motivation to engage with their academic work during isolation.…”
Section: Discussionmentioning
confidence: 93%
“…In line with these findings, early qualitative work suggests the pandemic has fostered opportunities for appreciation and gratitude by considering one's personal experience in comparison to others who have been adversely affected (i.e., relative fortune) and has increased time spent with family and engaging in new hobbies or activities [29]. However, burgeoning research has reported the negative impacts of the pandemic and national lockdowns on students' ability to regulate their attention and motivation levels [30] and to develop studying networks [31]. This was particularly true within our sample, with students reporting reduced motivation to engage with their academic work during isolation.…”
Section: Discussionmentioning
confidence: 93%
“…In the university context of the last two years, the transition from face-to-face to remote teaching, as a result of the limitations of the covid-19 pandemic, has strongly emphasized the need for students to possess pronounced selfmanagement skills in their learning processes in order not to fall behind on scheduled paths and deadlines and also to maintain a good level of perceived psychological well-being (Pelikan et al, 2021;Diotaiuti et al, 2021a). It has been observed in several studies how distractions at home and reduced social interaction with other students and faculty can negatively affect study time management and adaptation to the new emergency condition that requires students to have a higher level of autonomy and metacognitive control (Rasheed et al, 2020;Tezer, 2020;Alyami et al, 2021;Biwer et al, 2021;Diotaiuti et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of the students perceived a worsening of their learning skills during lockdown, and this is a noteworthy result, highlighting the serious effects of remote learning on students' perception of their abilities. Many factors were likely to contribute to the perception of this deterioration in study activities: the lack of appropriate devices or Internet connection lines, the absence of face-toface relationships with teachers and classmates, the reduced motivation in following lessons, as well as the difficulties linked to the new examination procedures (Biwer et al, 2021;Nguyen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%